(Bio)degradation of glyphosate in water-sediment microcosms – A stable isotope co-labeling approach. (1st August 2016) - Wang, Shizong; Seiwert, Bettina; Kästner, Matthias; Miltner, Anja; Schäffer, Andreas; Reemtsma, Thorsten; Yang, Qi; Nowak, Karolina M.
Abstract: Glyphosate and its metabolite aminomethylphosphonic acid (AMPA) are frequently detected in water and sediments. Up to date, there are no comprehensive studies on the fate of glyphosate in water-sediment microcosms according to OECD 308 guideline. Stable isotope co-labeled 13 C3 15 N-glyphosate was used to determine the turnover mass balance, formation of metabolites, and formation of residues over a period of 80 days. In the water-sediment system, 56% of the initial 13 C3 -glyphosate equivalents was ultimately mineralized, whereas the mineralization in the water system (without sediment) was low, reaching only 2% of 13 C-glyphosate equivalents. This finding demonstrates the key role of sediments in its degradation. Glyphosate was detected below detection limit in the water compartment on day 40, but could still be detected in the sediments, ultimately reaching 5% of 13 C3 15 N-glyphosate equivalents. A rapid increase in 13 C 15 N-AMPA was noted after 10 days, and these transformation products ultimately constituted 26% of the 13 C3 -glyphosate equivalents and 79% of the 15 N-glyphosate equivalents. In total, 10% of the 13 C label and 12% of the 15 N label were incorporated into amino acids, indicating no risk bearing biogenic residue formation from 13 C3 15 N-glyphosate. Initially, glyphosate was biodegraded via the sarcosine pathway related to microbial growth, as shown by co-labeled 13 C 15 N-glycine and biogenic residue formation. Later, degradation via AMPA dominated under starvation conditions, as shown by the contents of 13 C-glycine. The presented data provide the first evidence of the speciation of the non-extractable residues as well as the utilization of glyphosate as a carbon and nitrogen source in the water-sediment system. This study also highlights the contribution of both the sarcosine and the AMPA degradation pathways under these conditions. Highlights: First report on co-labeled 13 C3 15 N-glyphosate turnover in the water-sediment. Key role of the sediment-associated microbes in degradation of glyphosate. Sarcosine and AMPA pathway are relevant in the biodegradation of glyphosate. High content of AMPA might present an environmental risk. Nearly all NER were represented by non-toxic biogenic residues.